Teachers as the agent of change for student mental health: the role of teacher care and teacher support in Chinese students’ well-being - Wang, Tingting (Frontiers in Psychology, 2023)
Introduction: Students in any academic setting typically encounter a wide range of academic problems and challenges, which may endanger their mental health. Since the mental health or well-being of students directly affects their classroom performance, factors helping students overcome their academic challenges need to be widely researched. Considering this, extensive research has been carried out to uncover the personal and situational factors that help students solve their academic problems and improve their well-being. Moreover, due to the invaluable role of teachers in students’ mental conditions, several investigations to date have assessed the impact of teacher communicative behaviors on student well-being. Methods: To pursue this line of inquiry, the current research assessed the role of teacher support and teacher care in fostering Chinese students’ well-being. To do this, three self-report questionnaires were distributed to 338 undergraduate students. Then, Pearson product-moment and linear regression were performed through IBM SPSS Amos (Version 26) to analyze students’ answers to the self-report questionnaires. Results: The analysis outcomes divulged a series of strong and positive connections between teacher support, teacher care, and student well-being. The results also showed that teacher support and teacher care can significantly contribute to Chinese students’ well-being. Implications: Teachers and teacher educators may find these outcomes useful and informative.